PENGEMBANGAN MEDIA EMPATHYKIT BERDIFERENSIASI SEBAGAI UPAYA PENCEGAHAN PERUNDUNGAN PADA SISWA SEKOLAH DASAR - Gita Arya Ningsih; Urip Muhayat Wiji Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Empathykit media in differentiated learning as an effort to prevent bullying in elementary schools. The research employed a qualitative descriptive method involving a classroom teacher and sixth-grade students at SD Negeri Pleret Lor. The results showed that differentiated learning integrated with Empathykit media effectively addressed students' diverse learning needs, enhanced empathy awareness, and reduced the risk of bullying. The learning process included diagnostic assessments, grouping based on learning styles, and project-based tasks aligned with students’ interests and abilities. The success of the implementation was supported by teacher collaboration, adequate school facilities, and reference materials from the Merdeka Mengajar Platform. Empathykit has proven to be an innovative